Adaptive trajectory tracking controller for quadrotor systems subject to parametric uncertainties. Issue 15 (October 2017) - Zou, Yao; Zhu, Bing
Abstract: This paper investigates the trajectory tracking problem of quadrotor systems in the presence of uncertain inertial parameters. The controller is based on the hierarchical control strategy. The main features of this research include: (i) the command control of the position loop is synthesized with a saturation scheme, and a novel immersion & invariance (I&I) adaptation methodology is designed such that the mass estimation converges asymptotically to its real value; (ii) as an intermediate step, the command rotation matrix is extracted from the command control without the singularity; (iii) in terms of the rotation matrix property, the applied torque with appropriate control parameters and initial conditions is exploited for the attitude loop; and (iv) the projection algorithm is used to guarantee the inertial matrix estimation evolving within a prescribed range. It is proven based on the hierarchical system theory that, the developed controller enables the quadrotor system to track the reference trajectory asymptotically. Simulations are provided to support the proposed theoretical results.